Analisis Fitokimia Dan Uji Aktivitas Antibakteri Ekstrak Metanol Daun Suji (Pleomle Angusitolia N.E Brown) - Lutfiana Devi Kurnia; Ritbey Ruga; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Phytochemical and antibacterial activity assay of methanol extract from Suji leaves (Pleomele angustifolia) were carried out. The aims of this study are to determine secondary metabolites and antibacterial activity of the methanol extract against Streptococcus sobrinus KCCM 11898 and Streptococcus mutans ATCC 25175 by using agar well diffusion. The results showed that methanol extract of suji leaves contain phenolic, triterpenoid and steroid constituents. With 2%, the methanol extract displayed antibacterial activity against Streptococcus sobrinus and Streptococcus mutans with diameter inhibition zones of 19.0 and 10.3 mm, respectively.